Evaluation of customer satisfaction in hypermarkets: the impact of national culture and SERVQUAL dimensions - Veloso, Cláudia M. (2017)
The importance of the retail industry for the Portuguese economy coupled with the criticality of the retailing market for its growth and the relationship between service quality and effectiveness of business deliver the motivation for this study. The aims of this research focus on the intend to develop a methodology for assessing the impact of service quality in hypermarkets of Bragança city on customer satisfaction and behavioural intentions and to specifically comprehend a conceptual model to analyse if (1) the national culture directly influences the perceived service quality (in the five dimensions of SERVQUAL) and indirectly contributes to customer satisfaction and (2) this impacts directly on the intent to return and recommend services and if the intention to return directly influences the recommendation of services. This research is of particular importance to the literature retailing and practitioners, once there are a few studies in this field applied to the Portuguese hypermarkets retailing.